The Pros and Cons of Use of Handheld Electronic Devices During Ward Rounds and the Impact of the COVID-19 Pandemic - Shireen Suliman (13554986) (2023)
Purpose The exponential use of handheld electronic devices (HEDs) among healthcare providers has shown the potential to enhance clinical workflows and improve patient care. However, the challenges and risks of carrying these devices during ward rounds and their impact on postgraduate trainees’ (PGTs’) training in general and more specifically during the COVID-19 pandemic need to be explored. Methods A cross-sectional mixed-methods online survey was conducted to evaluate the perceptions of trainees and faculty at Accreditation Council for Graduate Medical Education International accredited residency and fellowships programs in Qatar on the use of HEDs on clinical workflow, trainees’ education, and the impact of the COVID-19 pandemic. One hundred and fifty-eight participants were enrolled in the study (87 postgraduate trainees and 71 faculty). Exploratory data analysis and descriptive statistics were performed using STATA version 12 and thematic analysis of 301 qualitative responses to the survey open-ended questions using Atlas. ti qualitative software, version 9.4.0. Results Almost all PGTs, 83 (95.4%), and faculty 43 (62.3%) use HEDs during ward rounds. Accessibility of patient information by PGTs 73 (94.8%) and faculty 46 (84.4%) and work efficiency were the main perceived benefits. Hindering communication between team members, disruption of interaction with patients, increased risk of infection and breach of patient confidentiality were among the challenges associated with their use. Carrying devices reduced the frequency of hand hygiene practices and physical examinations of patients by trainees. The COVID-19 pandemic led to a decrease in the use of HEDs by both faculty [38(64%)] and PGTs [42(60%)]. Conclusion HEDs’ use is valued by both faculty and PGTs in enhancing workflow, trainees’ education, patient experience, and patient care during the COVID-19 pandemic. Graduate medical education leaders should adopt measures to monitor their use during ward rounds as they can negatively impact trainees’ education, reduce interaction with patients, increase the risk of infection, and breach patient confidentiality. Other Information Published in: Advances in Medical Education and Practice License: https://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.2147/amep.s395501